Effects of Nitrogen Supply on Water Stress and Recovery Mechanisms in Kentucky Bluegrass Plants - Saud, Shah; Fahad, Shah; Yajun, Chen; Ihsan, Muhammad Z.; Hammad, Hafiz M.; Nasim, Wajid; Amanullah,; Arif, Muhammad; Alharby, Hesham (Frontiers in Plant Science, 2017)
Non-irrigated crops in temperate and irrigated crops in arid regions are exposed to an incessant series of drought stress and re-watering. Hence, quick and efficient recuperation from drought stress may be amongst the key determinants of plant drought adjustment. Efficient nitrogen (N) nutrition has the capability to assuage water stress in crops by sustaining metabolic activities even at reduced tissue water potential. This study was designed to understand the potential of proper nutrition management by studying the morphological and physiological attributes, and assimilation of nitrogen in Kentucky bluegrass under drought stress. In present study, one heterogeneous habitat and four treatments homogenous habitats each with four replications were examined during field trial. Drought stress resulted in a significant reduction in the nitrogen content of both mother and first ramets, maximum radius, above and below ground mass, number of ramets per plot, leaf water contents and water potential and increased the carbon content and the C:N ratio in both homogenous and heterogeneous plots compared to well-watered and nutritional conditions. Observation using electron microscopy showed that drought stress shrunk the vessel diameter, circumference and xylem area, but increased the sieve diameter, and phloem area in the leaf crosscutting structure of Kentucky bluegrass, first, second and third ramet leaf. Thus, it can be concluded that water stress markedly reduced all the important traits of Kentucky bluegrass however proper nutritional management treatment resulted in the best compensatory performance under drought assuaging its adversity up to some extent and may be considered in formulating good feasible and cost-effective practices for the environmental circumstances related to those of this study.